2017
DOI: 10.21511/ppm.15(1-1).2017.04
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the perceptions of institutional environment on entrepreneurial plans: exploring the moderating effects of firm age and firm size in Bulgarian enterprises

Abstract: (2017)The influence of the perceptions of institutional environment on entrepreneurial plans: exploring the moderating effects of firm age and firm size in Bulgarian enterprises AbstractIt was acknowledged that institutional environment plays an important role for shaping entrepreneurial behavior in transition economies. The present study investigates the influence of entrepreneurs' perceptions of institutional environment on their entrepreneurial plans in a large representative sample from a transition econom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…It concluded that the regulative system has a moderate relationship, whereas administrative regulations negatively affect growth intentions. Vladimirov, Davidkov and Yordanova (2017) studied the effects of the institutional environment on the entrepreneur growth plans among 1090 Bulgarian entrepreneurs using the structured interviews and survey methodology.…”
Section: Growth Intentionmentioning
confidence: 99%
“…It concluded that the regulative system has a moderate relationship, whereas administrative regulations negatively affect growth intentions. Vladimirov, Davidkov and Yordanova (2017) studied the effects of the institutional environment on the entrepreneur growth plans among 1090 Bulgarian entrepreneurs using the structured interviews and survey methodology.…”
Section: Growth Intentionmentioning
confidence: 99%
“…Furthermore, how individuals view institutions and governance matters; entrepreneurs who perceive the attitudes of local authorities toward private business as positive and supportive are more likely to report plans for expanding their current activities (Vladimirov et al, 2017). Societies where citizens view formal institutions as bureaucratic or highly corrupt, like Kosovo, entrepreneurial activity is reduced as entrepreneurs incur heavy costs from participating in economic activity that their benefits are ultimately reduced or alienated (Williams and Vorley, 2017).…”
Section: Entrepreneurship and Institutional Qualitymentioning
confidence: 99%